PRODUCTION OF ENVIRONMENTAL FRIENDLY FUEL IN INDONESIAN REFINERY - A.S. Nasution; Oberlin Sidjabat; Abdul Gafar; Rasdinal Ibrahim; Morina Morina (Scientific Contributions Oil and Gas, 2005)
Worldwide crude supplies are experiencing a mod- est trend toward heavier and high sulfur content. The average annual demand growth rate for light products (gasoline, kerosene and diesel oil) is higher than that for residual fuel oil, Therefore, converting additional bot- toms into light product by either thermal or catalytic pro- cesses will be needed. Vehicles and fuels have been developed simulta- neously and nowadays vehicles demand a very sophisti- cated fuel indeed. Environmental restriction, and efforts to minimize the pollutant problem by exhaust gases are causing design and changes in cars that in turn are hav- ing some effects on fuel quality. To reduce exhaust emission by fuel combustion, the specification of gasoline and diesel oil is now stricter. Various term in the models address qualities of the re- formulated gasoline, such as benzene, total aromatics and olefin content, RVP, the T of distillation range, sul- fur content, and oxygenate contents (Table 1)18.13.16). Diesel oil specification is limited as follows: aromatics, polyaromatics, sulfur content, T and cetane number (Table 2) (19.23,26) To improve the specification of commercial gasoline into the stricter specification of reformulated gasoline, refiners are forced in install new facilities to increase the production for high-octane mogas components. For the stricter diesel oil specification in the years 2000's, over 50% by volume of the total gas oil components (ex- cept hydrocracked gas oil) must undergo improvement by hydrotreating processes in order to achieve a suitable specification. In Indonesia, there are seven refineries with total crude oil capacity of 1,063 MBCD to produce fuel oils, lube base stocks and petrochemical products. Process- ing units and fuel oil production in Indonesia's refineries are given in Table 3 and 4, respectively. The production of gasoline and diesel oil components is review in this paper. Influence of hydrocarbon composition of those fuel components on their performances is discussed. A brief discussion is offered on the impact of the changing specification of gasoline and diesel oil on the refinery configuration.